FASHION BUSINESS COMPETITION ACCORDING TO LAW NO. 5 OF 1999 AND SHARIA ECONOMIC LAW: A STUDY ON FASHION STORES IN ACEH MARKET - Jannah, Khairatul; Husnul, Muhammad (JURISTA: Jurnal Hukum dan Keadilan, 2024)
Business competition requires the tenacity of business actors to exist so that they can survive the development of businesses that continue to compete rapidly in the era of technological progress. In the sale and purchase transaction, of course, there is mabi', which is the object of legal sale and purchase. Mabi' as the object of sale and purchase has conditions that must be met by the seller, such as clear and standardised object quality in the sale and purchase transaction. In the general substance of Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, efforts made by the government to minimize normal market mechanisms, namely giving licences to new companies to create competition as a form of democracy for the economy, increasing offers on goods with products that tend to be the same in fulfilling the free right to choose consumers. This type of research is a qualitative, descriptive approach through case studies. The efforts of fashion traders to make an adjustment process with several stages, namely adaptive, motivation and attitude towards the realistic present,. And the efforts of fashion traders in surviving in the world of online market competition to make a profit are that they must have a large enough initial capital to be able to start a business and must think about a place to sell and a sales marketing strategy through a marketplace platform or other online sales, and must apply a mixed approach by integrating conventional offline and online marketing in order to help traders reach various types of consumers.